Heckler & Koch and the systematic attacks on Ayotzinapa (Mexico) students - Del Rivero Del Rivero, José Alberto (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
This paper demonstrates how human rights violations and the commission of international crimes within underdeveloped and emerging countries can be caused by great power countries. In specific, it analyzes how weapons of war manufactured by the German company, Heckler & Koch were used to attack normal-school students from Ayotzinapa in Mexico, by municipal police. Additionally, it studies what the purpose of using these weapons of war was, who the responsible might be, and how these facts can be judged